Bardet-Biedl syndrome-7 (BBS7) shows treatment potential and a cone-rod dystrophy phenotype that recapitulates the non-human primate model. (4th May 2021) - Aleman, Tomas S.; O'Neil, Erin C.; O'Connor, Keli; Jiang, Yu You; Aleman, Isabella A.; Bennett, Jean; Morgan, Jessica I. W.; Toussaint, Brian W.
ABSTRACT: Purpose : To provide a detailed ophthalmic phenotype of two male patients with Bardet-Biedl Syndrome (BBS) due to mutations in the BBS7 gene Methods : Two brothers ages 26 (Patient 1, P1) and 23 (P2) underwent comprehensive ophthalmic evaluations over three years. Visual function was assessed with full-field electroretinograms (ffERGs), kinetic and chromatic perimetry, multimodal imaging with spectral domain optical coherence tomography (SD-OCT), fundus autofluorescence (FAF) with short- (SW) and near-infrared (NIR) excitation lights and adaptive optics scanning light ophthalmoscopy (AOSLO). Results : Both siblings had a history of obesity and postaxial polydactyly; P2 had diagnoses of type 1 Diabetes Mellitus, Addison's disease, high-functioning autism-spectrum disorder and −12D myopia. Visual acuities were better than 20/30. Kinetic fields were moderately constricted. Cone-mediated ffERGs were undetectable, rod ERGs were 80% of normal mean. Static perimetry showed severe central cone and rod dysfunction. Foveal to parafoveal hypoautofluorescence, most obvious on NIR-FAF, co-localized with outer segment shortening/loss and outer nuclear layer thinning by SD-OCT, and with reduced photoreceptors densities by AOSLO. A structural-functional dissociation was confirmed for cone- and rod-mediated parameters. Worsening of the above abnormalities was documented by SD-OCT and FAF in P2 at 3 years. Gene screening identified compound heterozygous mutations in BBS7 (p.Val266Glu: c.797 T > A of maternal origin; c.1781_1783delCAT, paternal) in both patients. Conclusions : BBS7 -associated retinal degeneration may present as a progressive cone-rod dystrophy pattern, reminiscent of both the murine and non-human primate models of the disease. Predominantly central retinal abnormalities in both cone and rod photoreceptors showed a structural-functional dissociation, an ideal scenario for gene augmentation treatments.